2003
DOI: 10.1577/1548-8659(2003)132<0326:pojcsa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Juvenile Chinook Salmon and other Fish Species through Archimedes Lifts and a Hidrostal Pump at Red Bluff, California

Abstract: Fish were passed through two large Archimedes lifts and a large Hidrostal pump at the U.S. Bureau of Reclamation's experimental pumping plant on the upper Sacramento River, California. Two of the pumps were run concurrently during trials to compare their effects on hatchery-reared juvenile chinook salmon Oncorhynchus tshawytscha. In each trial, control samples were released at pump outfalls, and treatment samples were inserted into the intake of each pump. Fish in samples were collected in downstream holding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…McNabb et al . () and Durif et al . () reported that large fish and eel are more likely to be impacted by physical strike with mechanical components.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…McNabb et al . () and Durif et al . () reported that large fish and eel are more likely to be impacted by physical strike with mechanical components.…”
Section: Discussionmentioning
confidence: 94%
“…These PSs play an important role in wetland drainage, irrigation, water diversion, agriculture, drinking water provision, flood protection, water level control, the conservation of polder areas and may even belong to a country's cultural–historical heritage (McNabb et al . ; Baumgartner et al . ; Grimaldo et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, large fish have a greater capacity to resist shear forces (Nietzel et al. 2004) and are more likely to be impacted by physical strike with mechanical components (McNabb, Liston & Borthwick 2003). This assertion is supported by the observed increase in mortality among large fish (>200 mm) and the proportion of fish that lost tails, were cut in half or decapitated during passage.…”
Section: Discussionmentioning
confidence: 99%
“…Small fish have poor swimming abilities, a reduced body size and are likely to be more susceptible to the effects of sudden pressure changes and shear stress associated with passage through a pump system (Neitzel, Richmond, Dauble, Mueller, Morsund, Abernethy, Guensch & Cada 2000). By contrast, large fish have a greater capacity to resist shear forces (Nietzel et al 2004) and are more likely to be impacted by physical strike with mechanical components (McNabb, Liston & Borthwick 2003). This assertion is supported by the observed increase in mortality among large fish (>200 mm) and the proportion of fish that lost tails, were cut in half or decapitated during passage.…”
Section: Discussionmentioning
confidence: 99%